A biclustering approach for classification with mislabeled data. Issue 12 (15th July 2015) - de França, Fabrício O.; Coelho, André L.V.
Highlights We propose a biclustering approach (BicNoise) for coping with mislabeled data. We assess three variants of BicNoise on binary classification problems. The proposed strategy is mostly useful when high levels of noise take place.